On markedness in locative and existential predication: “Existential takeover”, frequency and complexity in Siberian languages - Chris Lasse Däbritz (Linguistic Typology at the Crossroads)
The present paper investigates existential and locative clauses in fourteen Siberian languages. It is shown that all of them exhibit patterns of so-called “existential takeover”, i.e. originally existential items occurring in locative predication. Starting from the observation that locative predication is frequently viewed as ontologically primary and unmarked against existential predication, these existential takeover patterns are unexpected. Considering the text frequency and pragmatics of locative and existential predication, the paper argues that a markedness-based approach to these domains is unfeasible and leads to false predictions and generalisations. Following from this, it argues that a general typology of locative and existential predication must not contain any a priori restrictions regarding the observed linguistic realisations. Moreover, it proposes a two-layered design of such a typology which considers both the domains themselves as well as possible co-expression patterns.